The validation of 3D virtual comparison microscopy (VCM) in the comparison of expended cartridge cases. Issue 2 (22nd November 2021) - Knowles, Laura; Hockey, Daniel; Marshall, John
Abstract: In this study, the Cadre TopMatch‐3D scanner and associated virtual comparison software was evaluated to determine whether this technique is a valid and reliable method of conducting cartridge component comparisons. That is, if virtual comparison microscopy (VCM) produces results at least equivalent to those generated through traditional light comparison microscopy (LCM), the method would be deemed valid for use in an operational setting. Particular emphasis was placed on the capability to render same source conclusions. Of the 40 true identifications available to each examiner, corresponding to a total of 520 comparisons, positive identifications were made more frequently using VCM as compared to traditional LCM where inconclusive conclusions were provided at a higher rate. VCM produced a higher sensitivity (88.41%) and specificity (13.64%) rate than LCM, 80.08% and 12.50%, respectively. Based on the findings of the study, considered together with the benefits that VCM offers in the name of efficiency, it became apparent that Cadre's 3D scanning microscope and its associated virtual comparison software tested in this study is an appropriate and valid technique for conducting comparisons of expended cartridge cases and can be implemented into routine casework for that purpose.